An “Omic” Overview of Fragile X Syndrome - Dionne, Olivier (Biology (Basel), 2021)
SIMPLE SUMMARY: Fragile X syndrome (FXS) is a neurodevelopmental disorder and remains the most frequent inherited cause of intellectual disability. Fragile X patients are at great risk to develop behavior problems including autism, anxiety, aggressivity and hyperactivity. FXS results from a mutation leading to the absence of a single protein, the fragile X mental retardation protein (FMRP). Most studies aiming to understand the physiopathology of FXS are centered on the effect of its absence on protein synthesis. However, besides protein synthesis regulation, FMRP has several other functions that need to be understood and could play a significant role in FXS. The goal of the present work is to review some of these functions and to put them into perspective in order to get a more comprehensive understanding of FXS physiopathology. ABSTRACT: Fragile X syndrome (FXS) is a neurodevelopmental disorder associated with a wide range of cognitive, behavioral and medical problems. It arises from the silencing of the fragile X mental retardation 1 (FMR1) gene and, consequently, in the absence of its encoded protein, FMRP (fragile X mental retardation protein). FMRP is a ubiquitously expressed and multifunctional RNA-binding protein, primarily considered as a translational regulator. Pre-clinical studies of the past two decades have therefore focused on this function to relate FMRP’s absence to the molecular mechanisms underlying FXS physiopathology. Based on these data, successful pharmacological strategies were developed to rescue fragile X phenotype in animal models. Unfortunately, these results did not translate into humans as clinical trials using same therapeutic approaches did not reach the expected outcomes. These failures highlight the need to put into perspective the different functions of FMRP in order to get a more comprehensive understanding of FXS pathophysiology. This work presents a review of FMRP’s involvement on noteworthy molecular mechanisms that may ultimately contribute to various biochemical alterations composing the fragile X phenotype.